Non-cell autonomous and spatiotemporal signalling from a tissue organizer orchestrates root vascular development - Yang, BaoJun; Minne, Max; Brunoni, Federica; Plačková, Lenka; Petřík, Ivan; Sun, Yanbiao; Nolf, Jonah; Smet, Wouter; Verstaen, Kevin; Wendrich, Jos R; Eekhout, Thomas; Hoyerová, Klára; et al. (Nature plants, 2021)
During plant development, a precise balance of cytokinin is crucial for correct growth and patterning, but it remains unclear how this is achieved across different cell types and in the context of a growing organ. Here we show that in the root apical meristem, the TMO5/LHW complex increases active cytokinin levels via two cooperatively acting enzymes. By profiling the transcriptomic changes of increased cytokinin at single-cell level, we further show that this effect is counteracted by a tissue-specific increase in CYTOKININ OXIDASE 3 expression via direct activation of the mobile transcription factor SHORTROOT. In summary, we show that within the root meristem, xylem cells act as a local organizer of vascular development by non-autonomously regulating cytokinin levels in neighbouring procambium cells via sequential induction and repression modules.
Keywords: Cytokinins; signální transdukce; transkripční faktory bHLH; oxidoreduktasy; Arabidopsis; proteiny huseníčku; Signal Transduction; Trans-Activators; Arabidopsis Proteins; kořeny rostlin; Plant Roots; Oxidoreductases; trans-aktivátory; cytokininy; Basic Helix-Loop-Helix Transcription Factors